Respuesta :
(2/9) - (3/9 + 5/9)
2/9 - 8/9
-6/9.
Simplified, it is - 2/3. Hope it helps! :)
2/9 - 8/9
-6/9.
Simplified, it is - 2/3. Hope it helps! :)
Step 1; Write Out the Problem
(2/9) - (1/3 + 5/9) = ?
Step 2; Perenthesis First/Make the Dinominator the Same
(2/9) - (3/9 + 5/9) = ?
Step 3; Add
(2/9) - (8/9) = ?
Step 4; Take Out the Perenthesis
2/9 - 8/9 = ?
Step 5; Subtract
2/9 - 8/9 = 6/9
Step 6; Write Out the Whole Answer
(2/9) - (1/3 + 5/9) = 6/9
Nice
(2/9) - (1/3 + 5/9) = ?
Step 2; Perenthesis First/Make the Dinominator the Same
(2/9) - (3/9 + 5/9) = ?
Step 3; Add
(2/9) - (8/9) = ?
Step 4; Take Out the Perenthesis
2/9 - 8/9 = ?
Step 5; Subtract
2/9 - 8/9 = 6/9
Step 6; Write Out the Whole Answer
(2/9) - (1/3 + 5/9) = 6/9
Nice